Icariin inhibits epithelial mesenchymal transition of renal tubular epithelial cells via regulating the miR-122-5p/FOXP2 axis in diabetic nephropathy rats - Li Zang; Fang Gao; Aijing Huang; Yalan Zhang; Yangyan Luo; Lijia Chen; Nan Mao (Elsevier, 2022)
Epithelial mesenchymal transition (EMT) of renal tubular epithelial cells (RTECs) dominates the pathology of diabetic nephropathy (DN). microRNAs (miRNAs) can influence the fate of DN via regulation of EMT. This study aimed to analyze the role of Icariin (ICA) in EMT of RTECs, hoping to provide theoretical basis for DN management. The DN rat model was established using streptozocin, followed by ICA treatment, histopathological observation, and detection of creatinine and blood urea nitrogen. In vitro cell models were established using high glucose (HG), followed by assessment of cell proliferation, apoptosis, and migration, and E-cadherin, α-SMA, miR-122-5p, and FOXP2 expressions. Cells were transfected with miR-122-5p mimics or si-FOXP2 for joint experiments with ICA. The targeting relationship between miR-122-5p and FOXP2 was verified. ICA repaired renal dysfunctions and glomerular structure abnormities of DN rats in a dose-dependent manner. In vitro, ICA improved proliferation while suppressed migration, apoptosis, and EMT of RTECs. miR-122-5p was up-regulated in DN rats and suppressed by ICA, and miR-122-5p targeted FOXP2. miR-122-5p up-regulation or FOXP2 down-regulation reversed the protective effects of ICA on HG-induced RTECs. Overall, our finding ascertained that ICA inhibited miR-122-5p to promote FOXP2 transcription, thereby attenuating EMT of RTECs and renal injury in DN rats.